1999
DOI: 10.1093/ajcn/69.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial lipid, glucose, insulin, and cholecystokinin responses in men fed barley pasta enriched with β-glucan

Abstract: Background: Fiber regulates the rate and site of lipid and carbohydrate digestion and absorption and thus can modify the alimentary responses to a meal. When fiber sources containing viscous polysaccharides are included in a meal, a slower rate of carbohydrate and lipid absorption will modify the alimentary hormone and lipid responses. Objective: We investigated in 11 healthy men the response of insulin, glucose, cholecystokinin, and lipid to 2 test meals containing ␤-glucan. Design: One of the meals was high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
139
0
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(155 citation statements)
references
References 42 publications
6
139
0
8
Order By: Relevance
“…Previous studies (Anderson et al, 1990;Hallfrisch & Behall, 2000;Keogh et al, 2003) have shown that the delayed glucose absorption probably is due to the high viscosity of b-glucans. Bourdon et al (1999) demonstrated that there was no significant difference in the glucose response between a meal with enriched barley pasta (5 g of b-glucans) and wheat pasta, but the insulin response differed. Though this indicates that carbohydrate from the meal with b-glucan enriched pasta was digested and absorbed more slowly, the effect was not enough to lower the glycaemic response.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies (Anderson et al, 1990;Hallfrisch & Behall, 2000;Keogh et al, 2003) have shown that the delayed glucose absorption probably is due to the high viscosity of b-glucans. Bourdon et al (1999) demonstrated that there was no significant difference in the glucose response between a meal with enriched barley pasta (5 g of b-glucans) and wheat pasta, but the insulin response differed. Though this indicates that carbohydrate from the meal with b-glucan enriched pasta was digested and absorbed more slowly, the effect was not enough to lower the glycaemic response.…”
Section: Discussionmentioning
confidence: 95%
“…These varying results in human trials may be due to factors such as the dose of b-glucans, food processing, solid or liquid study products, the initial cholesterol concentrations of the subjects, or the study design. Although the cholesterol-lowering mechanisms of oats and barley b-glucans are still not fully understood, their effects seem to relate to an increased viscosity in the intestine, which leads to a decreased cholesterol absorption Lia et al, 1995;Bourdon et al, 1999). The viscosity in the intestine not only depends on the amount of b-glucan ingested, but also on the solubility, structure and MW of the b-glucan (Å man et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies increased b-glucan intake as part of their soluble fiber strategy and further demonstrated the therapeutic potential of viscous fibers such as oat bglucan. Studies have shown that barley b-glucan also reduces the post-prandial glucose and endocrine response (Bourdon et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The role of viscosity of b-glucan in reducing the postprandial blood glucose levels is well documented in experimental studies (Wood et al, 1990(Wood et al, , 1994(Wood et al, , 2000Braaten et al, 1991;Bourdon et al, 1999). Wood et al (1994) used increasing doses of pure and totally dissolved oat b-glucan to show that the oat gum decreases postprandial glucose and insulin responses.…”
Section: Introductionmentioning
confidence: 99%